Synthetic anti-angiogenic genomic therapeutics for treatment of neovascular age-related macular degeneration - Jing Wang (Elsevier, 2021)
In light of the intriguing potential of anti-angiogenic approach in suppressing choroidal neovascularization, we attempted to elaborate synthetic gene delivery systems encapsulating anti-angiogenic plasmid DNA as alternatives of clinical antibody-based therapeutics. Herein, block copolymer of cyclic Arg-Gly-Asp-poly(ethylene glycol)-poly(lysine-thiol) [RGD-PEG-PLys(thiol)] with multifunctional components was tailored in manufacture of core-shell DNA delivery nanoparticulates. Note that the polycationic PLys segments were electrostatically complexed with anionic plasmid DNA into nanoscaled core, and the tethered biocompatible PEG segments presented as the spatial shell (minimizing non-specific reactions in biological milieu). Furthermore, the aforementioned self-assembly was introduced with redox-responsive disulfide crosslinking due to the thiol coupling. Hence, reversible stabilities, namely stable in extracellular milieu but susceptible to disassemble for liberation of the DNA payloads in intracellular reducing microenvironment, were verified to facilitate transcellular gene transportation. In addition, RGD was installed onto the surface of the proposed self-assemblies with aim of targeted accumulation and internalization into angiogenic endothelial cells given that RGD receptors were specifically overexpressed on their cytomembrane surface. The proposed anti-angiogenic DNA therapeutics were validated to exert efficient expression of anti-angiogenic proteins in endothelial cells and elicit potent inhibition of ocular neovasculature post intravitreous administration. Hence, the present study approved the potential of gene therapy in treatment of choroidal neovascularization. In light of sustainable gene expression properties of DNA therapeutics, our proposed synthetic gene delivery system inspired prosperous potentials in long-term treatment of choroidal neovascularization, which should be emphasized to develop further towards clinical translations.